2017
DOI: 10.1111/jfd.12768
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity assessment of sea lice to chemotherapeutants: Current bioassays and best practices

Abstract: Traditional bioassays are still necessary to test sensitivity of sea lice species to chemotherapeutants, but the methodology applied by the different scientists has varied over time in respect to that proposed in "Sea lice resistance to chemotherapeutants: A handbook in resistance management" (2006). These divergences motivated the organization of a workshop during the Sea Lice 2016 conference "Standardization of traditional bioassay process by sharing best practices." There was an agreement by the attendants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Studies carried out to assess efficacy of the medicines used in the control of C. rogercresseyi and to monitor resistance through the bioassay applications have demonstrated that females are less susceptible than males to pyrethroids, organophosphates, and hydrogen peroxide 88–90,94 . The same has been observed in the field, with a higher proportion of females surviving the antiparasitic treatment, with a higher abundance of females, which can reach over 70% of total lice abundance on the fish (Bravo, personal observation).…”
Section: Sea Lice Control Methodsmentioning
confidence: 84%
“…Studies carried out to assess efficacy of the medicines used in the control of C. rogercresseyi and to monitor resistance through the bioassay applications have demonstrated that females are less susceptible than males to pyrethroids, organophosphates, and hydrogen peroxide 88–90,94 . The same has been observed in the field, with a higher proportion of females surviving the antiparasitic treatment, with a higher abundance of females, which can reach over 70% of total lice abundance on the fish (Bravo, personal observation).…”
Section: Sea Lice Control Methodsmentioning
confidence: 84%
“…Similarly, in Plutella xylostella pyrethroid exposure induced time-dependent alterations of carboxylesterase-6 mRNA expression levels within 3 to 48 h ( Li et al, 2021 ). The design of exposure experiments in this report was aligned to recommendations for internationally standardized sea louse bioassays with DTM and EMB ( Marín et al, 2018 ; Sevatdal and Horsberg, 2003 ; Westcott et al, 2008 ), allowing to compare results to those of other reports. In addition, in a previous study short EMB exposures (1−3 h) resulted in very few transcripts being up- or down regulated ( Carmichael et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adult parasite samples of C. rogercresseyi corresponded to two previously characterized strains with contrasting sensitivities to the antiparasitic drug azamethiphos (Nuñez-Acuña et al, 2020). The sensitivity to this drug was tested through a specific bioassay validated for this species, representing drug resistance/ susceptibility as the EC 50 index, effective drug concentration affecting 50% of the population (SEARCH C, 2006;Marıń et al, 2018), and the efficacy in field treatments in salmon farms. The selected resistant strain had an EC 50 index of 13.72 and azamethiphos treatment efficacy in salmon farms < 60%, while the susceptible population had EC 50 of 0.4778 and in-field treatment efficacy > 92%.…”
Section: Sea Lice Samples and Culture Conditionsmentioning
confidence: 99%